Food Insecurity and Obesity - Rachel Savelle; LaToya J. O'Neal (EDIS)
Food insecurity is prevalent across the US and often coexists with obesity. It is important that the coexistence of food insecurity and obesity is well understood so that community outreach programs and interventions can continue to be implemented in order to improve food security by increasing access to affordable, healthy foods and promoting good health nationwide. This 4-page fact sheet discusses food insecurity, reduced access to healthy food options, the cycle of food excess and deprivation, SNAP, the WIC program, and child nutrition programs. Written by Rachel Savelle and LaToya J. O'Neal, and published by the UF Department of Family, Youth and Community Sciences, February 2017.